Evaluation of Program Inputs (Financing, Human Resources, Infrastructure, and Guidelines) in the URC-KISS Policy for Stunting Reduction in North Konawe Regency - Rati Rati; Sartini Risky; Sanihu Munir (Waluya The International Science of Health Journal, 2026)
Introduction: Stunting is a chronic nutritional problem affecting children and remains a major public health issue in Indonesia. The prevalence of stunting in North Konawe Regency was 21.6% in 2022 and increased to 25.6% in 2023. One of the policy efforts implemented by the North Konawe Regency Government is the URC-KISS program (Rapid Response Unit for Extreme Poverty, Inflation, and Stunting). However, the effectiveness of this policy has not yet been evaluated. This study aimed to evaluate the input components of the URC-KISS policy in efforts to reduce stunting rates. Method: This study used a qualitative approach with a case study design. A total of twelve informants were recruited, consisting of two key informants and ten supporting informants. Informants were selected using snowball sampling techniques. Data were analyzed manually through data reduction, data display, and conclusion drawing. Result: The findings show that program inputs include financing provided directly by the local government, adequate human resources with appropriate competencies, and infrastructure such as operational vehicles and anthropometric measurement tools. In addition, program implementation is supported by official guidelines for stunting reduction in North Konawe Regency. Conclusion: The URC-KISS program is supported by adequate inputs, including funding, human resources, infrastructure, and implementation guidelines, which contribute to efforts to reduce stunting rates in North Konawe Regency.